An improved formula for the inductance of mesh grids. Issue 9 (September 2017) - Manoochehri, Omid; Salari, Mohammad Ali; Darvazehban, Amin
Abstract: An improved formula is introduced for calculating the inductance of a grid of wires or strips. Many existing formulas for the inductance of wire grids are simple; however, their simplicity limits the value of the width of the strip to the period of array ratio for which the formulas are applicable. This has motivated us to propose a higher order approximation to remove some limitations of the existing formulas for the grid impedance particularly at high frequencies. The mode matching method is used to obtain the grid impedance and the proposed formula, the result of the full wave HFSS simulation as well as the less accurate formula are compared and an improvement in the proposed formula, especially at high frequencies, is observed.